Cash waqf for financing ACT foundation in Indonesia: a juristic and analytical study - Akbar, Kieren; Karim, Fatimah (AL- Hikmah Research & Publication Centre, 2022)
Cash waqf is the most useful waqf instrument to be used in humanitarian institutions. This research aims to analyze cash waqf and its expedience in financing humanitarian relief institutions (ACT Foundation) and investment methods in the foundation. Thus, humanitarian activities necessitate a form of money distribution to preserve the continuation of its benefits. The researcher used inductive approach in evaluating legal evidences, information, data and details regarding cash waqf. Furthermore, analytical approach was used to analyze and explain the legal aspects of cash waqf and verify its legality and validation to finance humanitarian institutions. By integrating theory and practice, the researcher conducted a field study by interviewing officials in the institution to ensure that the practices are in accordance with Islamic jurisprudence. Also, the research was done to expose investment methods to gain benefits of cash waqf. It can be concluded that the cash waqf is allowed to finance the activities of humanitarian institution as well as being invested to obtain further benefits.